1980
DOI: 10.1007/bf02408527
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the bone-seeking agent99mTc-1-hydroxyethylidene-1,1-diphosphonic acid to cartilage and collagen in vitro and its stimulation by Er3+ and low pH

Abstract: The bone-seeking agent 99mTc-labeled 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP) unexpectedly binds to particles of human articular cartilage as well as cortical bone in vitro. Collagen also sequesters this compound, suggesting that collagen contributes to the uptake of 99mTc-HEDP by cartilage and bone. Particles of the bone mineral calcium hydroxyapatite also bind 99mTc-HEDP in vitro. Pretreatment of particles with Er3+ stimulates binding in each case. Lowering the pH of incubation to pH 2 has this effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Ions of the lanthanide series (Ln3+), which often serve as isomorphous replacements for Ca2+ in biochemical systems (Williams, 1979), have also been used. That Ln3+ might prove useful in the present context is suggested by previous work from this laboratory (Evans & Mears, 1980;Evans & Tew, 1981;Evans, 1981).…”
mentioning
confidence: 62%
“…Ions of the lanthanide series (Ln3+), which often serve as isomorphous replacements for Ca2+ in biochemical systems (Williams, 1979), have also been used. That Ln3+ might prove useful in the present context is suggested by previous work from this laboratory (Evans & Mears, 1980;Evans & Tew, 1981;Evans, 1981).…”
mentioning
confidence: 62%
“…Also of potential benefit in OA, bisphosphonates have effects beyond the osteoclast and may be slightly immunomodulating via inhibition of pro-inflammatory cytokines 2. In vitro, etidronate binds to human cartilage3 and can modestly inhibit matrix metalloproteinases 4. Neridronate stimulated osteoblasts to produce osteocalcin in an OA model, providing yet another potential pathway for bisphosphonate activity in OA 5.…”
mentioning
confidence: 99%
“…Previous histological studies 4,5,7 have confirmed the presence of increased osteoclastic activity with lymphocytic and plasma cell infiltration, which points to the use of bisphosphonates, as they have been found to exert slight immunomodulating effects by inhibiting pro‐inflammatory cytokines 34 . In vitro , bisphosphonates can bind to cartilage 35 and slightly inhibit matrix metalloproteinases 16 . In clinical trials examining the efficacy of bisphosphonates in OA, alendronate reduced MRI‐observed BMLs in a cohort of women but did not halt radiological progression 18 .…”
Section: Clinical Symptoms and Signs Associated With Bmlsmentioning
confidence: 91%